The DMT Gland: The Pineal, The Spirit Molecule, and Popular Culture - St. John, Graham (International journal for the study of new religions, 2016)
With clinical psychiatrist Rick Strassman's DMT: The Spirit Molecule as a vehicle, the pineal gland has become a popularly enigmatic organ that quite literally excretes mystery. Strassman’s top selling book documented ground-breaking clinical trials with the powerful mind altering compound DMT (N,N-dimethyltryptamine) conducted at the University of New Mexico in the early 1990s. Inflected with Buddhist metaphysics, the book proposed that DMT secreted from the pineal gland enables transit of the life-force into this life, and from this life to the next. Since that study, the hunt has been on to verify the organ’s status as the "lightening rod of the soul" and that DMT is the "brain's own psychedelic." While the burden of proof hangs over speculations that the humans produce endogenous DMT in psychedelic quantities, knowledge claims have left the clinic to forge a career of their own. Exploring this development, the article addresses how speculation on the DMT-producing "spirit gland"—the "intermediary between the physical and the spiritual"—are animate in film, literature, music and other popular cultural artefacts. Navigating the legacy of the DMT gland (and DMT) in diverse esoteric currents, it illustrates how Strassman’s "spirit molecule" propositions have been adopted by populists of polar positions on the human condition: i.e. the cosmic re-evolutionism consistent with Modern Theosophy and the gothic hopelessness of H. P. Lovecraft. This exploration of the extraordinary career of the "spirit molecule" enhances awareness of the influence of drugs, and specifically "entheogens," in diverse "popular occultural" narratives, a development that remains under-researched in a field that otherwise recognises that oc/cult fandom—science fiction, fantasy and horror—is a vehicle for religious ideas and mystical practices.